Crystal Structure and Theoretical Analysis of Cs2Ca3(SO4)4 - Penglin Fang; Wenyue Tang; Yaoguo Shen; Jinquan Hong; Yongming Li; Junrong Jia (Crystals, 2022)
Using the homovalent cation substitution strategy, a new sulfate, Cs2Ca3(SO4)4, was successfully prepared using the spontaneous crystallization technique. A single-crystal structure measurement suggested that it crystallizes in space group P21/c, with lattice parameters and molecules per unit cell of a = 9.9153(8), b = 9.3760(6), c = 9.8044(9), β = 118.365(3)°, V = 802.04(11), and Z = 2. In the structure of Cs2Ca3(SO4)4, CaO6 octahedra and SO4 tetrahedra are interconnected via a corner-sharing mode to form a three-dimensional framework comprising large cavities filled with Cs+ cations. First-principles calculations and diffuse reflectance spectra indicated that Cs2Ca3(SO4)4 has a large energy band gap. Moreover, structural comparisons with similar compounds were conducted to explain the role of cations in tuning structural symmetry and birefringence. This paper helps to explain the size effect of cations on structural evolution.